2001
DOI: 10.1038/sj.ijo.0801549
|View full text |Cite
|
Sign up to set email alerts
|

Plasma leptin concentrations and four-year weight gain among US men

Abstract: OBJECTIVE: Leptin, a primarily adipose tissue-derived protein product of the obesity (ob) gene, is an important regulator of energy metabolism. The strong association between body fat mass and elevated circulating leptin levels in humans suggests that leptin resistance, rather than leptin production, may contribute to the development of obesity and associated disorders. The purpose of this study is to evaluate the relationship between circulating plasma leptin levels and regulation of body weight over time amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 50 publications
4
40
1
Order By: Relevance
“…Hence hyperinsulinemia or hyperleptinemia will develop. This may explain why elevated leptin was associated with weight gain among obese subjects in our population 69 and why associations of HbA1c and sTNF-R on leptin concentrations were limited to overweight subjects. Similar to our results, in a study of 42 obese subjects and 16 controls, Corica et al 41 found an association between leptin and sTNF-R1 in obese participants; however, they did not have a measure of long-term glycemic status.…”
Section: Discussionmentioning
confidence: 88%
“…Hence hyperinsulinemia or hyperleptinemia will develop. This may explain why elevated leptin was associated with weight gain among obese subjects in our population 69 and why associations of HbA1c and sTNF-R on leptin concentrations were limited to overweight subjects. Similar to our results, in a study of 42 obese subjects and 16 controls, Corica et al 41 found an association between leptin and sTNF-R1 in obese participants; however, they did not have a measure of long-term glycemic status.…”
Section: Discussionmentioning
confidence: 88%
“…30 Moreover, in a prospective analysis of the Health Professionals Follow-Up Study of overweight men, weight gain over 4 years was associated with a high leptin level. 53 In conclusion, the weight loss intervention utilized in this study produced significant changes in body weight and in leptin concentrations at the 6-and 18-month follow-up. In contrast to some existing studies, exercise alone did not affect leptin concentrations.…”
Section: Discussionmentioning
confidence: 98%
“…Previously we found a direct association between plasma leptin concentrations and subsequent weight gain in a 4 y follow-up of 268 men. 14 This positive association was limited to overweight men (BMI!25 kgam 2 ), which suggests that hyperleptinemia coupled with leptin resistance may trigger weight gain among obese subjects. With the exception of large changes in obesity, few other factors have been identi®ed which can modify leptin concentrations (or leptin resistance).…”
Section: Introductionmentioning
confidence: 99%
“…14 Because hyperleptinemia may be associated with weight gain among overweight subjects, we conducted analyses strati®ed by obesity level to evaluate modi®able factors associated with leptin concentrations. Table 4 shows the mean ( AE s.d.)…”
Section: Multivariate Regression Models Of Dietary and Lifestyle Factmentioning
confidence: 99%